The RIGHTEOUS MEN Who Are WEAKEND by Al- AQILI In His BOOK 'The GREAD WEAK' – CRITICAL STUDY - - Hasan, Adeeb (Islamic Sciences Journal, 2023)
The research aimed to highlight the importance of leaning about wound science and modification, and their meanings of prouisions on men narrators. The attention of Sunna scholars with this section is not for argumentation, or of prouisions on men narrators. The research was sought to weaken one of the senior scientists of this science, is Imam aqili. So the research on the criticism of these provisions has repeatedly scheduled to score, in the way, in they.